Optimizing Port Development as an Economic Equity Policy in Underdeveloped Regions: A Case Study of Tapaleo, North Maluku - Apriyani, Gresia; Tumangger, Siti Sarah; Siregar, Sri Ramadhani; Situmeang, Romauli Br; Suyana Pandiangan, Bona Vintura (Indonesian Journal Publisher, 2026)
The development of ports in underdeveloped regions plays a strategic role in enhancing connectivity, accelerating economic distribution, and reducing interregional disparities. This study analyzes the development of Tapaleo Port in Central Halmahera, North Maluku, through the lens of public economics and equity-oriented policy. The research adopts a case study approach with an analytical framework based on market failure theory, positive externalities, the Lindahl financing model, and the Kaldor–Hicks welfare criterion. The findings indicate that the port’s development has generated positive impacts on the regional economy, including a 22% reduction in logistics costs, an 18% increase in fisheries exports, and contributions to local job creation. However, its implementation still faces several challenges, such as delays in budget absorption, limited readiness of supporting infrastructure, and inadequate community involvement. This study recommends improving governance transparency, strengthening cross-sectoral coordination, and adopting an inclusive development model that actively engages local communities to achieve long-term and sustainable economic equity.